Pentingnya Mengekspresikan Emosi Dengan Cara yang Sehat Untuk Mencapai Kesuksesan Dalam Kehidupan - Sri Mulyani; Sutrisno S (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This study aims to show the importance of expressing emotions in a healthy way in life properly and correctly, not to cause regrets and achieve success. Emotions are a normal expression of what happening in life. Being unable to express emotions make a numb, or avoid and give vent to addictive. Being unable to express emotions will be depressed for the rest of their lives and cause violent outbursts. This can be a barrier to success. Negative emotions are a sign that the body needed attention, and demands to be fulfilled. For this reason, a response must be healthy, so that it does cause bitterness, hurt, stress, depression, or even the desire to commit suicide. Self-awareness to always investigate the heart is the first step in detecting mental health. The process of restoring the heart is carried out with repentance, forgiveness, and reconciliation. Healthy mental can be expressed in positive emotions, including; joyful heart, humility, and gratitude. This research was conducted with literacy studies. Research results show that a person’s ability to express emotions healthily will help in finding an inner voice that is synergistic with God’s voice which is the real key to success.